Development of Interactive Compact Disk Learning Media with Caring For Living Things Theme - Eges Triwahyuni; I Kadek Suartama (EDUTEC : Journal of Education And Technology, 2021)
This research aims to design and make learning that is packed with Intractif CD to facilitate applying teachers to learning activities with the theme III caring for living creatures of animal and plant subtema in my home environment for grade IV elementary school odd semester. research place in Seskolah Dasar Negara 1 Kandang Kapongan Situbondo Regency with a total of 15 learners. With this research using the ADDIE development model (Analysis, Desagn, Develop, Implement,and Evaluate)bysourced on the results of research, it can be concluded that educational media packaged by Intractif CD with the theme of caring for living things meet the eligibility criteria with the field of media experts obtaining a value of 89.91% listed among the qualifications is very feasible and validation of the field of media experts obtained a value of 86.95% listed qualifications are very feasible, and the renponden in the feasibility and effectiveness of obtaining a value of 86.69% and vice versa effectiveness while effectiveness obtained a value of 85.90%.